A New Way to Find: Testing the Use of Clustering Topics in Digital Libraries - Hagedorn, Kat; Kargela, Michael; Noh, Youn; Newman, David (D-Lib magazine, 2011)
Describes two methods used to research the issue of how useful a topic modeling algorithm to find relevant materials in a large corpus of textual items is to end-users, utilising an instance of HathiTrust containing a snapshot of art, architecture and art history records from early 2010. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.